SacB-SacR Gene Cassette As the Negative Selection Marker to Suppress Agrobacterium Overgrowth in Agrobacterium-Mediated Plant Transformation - Liu, Yiming; Miao, Jiamin; Traore, Sy; Kong, Danyu; Liu, Yi; Zhang, Xunzhong; Nimchuk, Zachary L.; Liu, Zongrang; Zhao, Bingyu (Frontiers in Molecular Biosciences, 2016)
Agrobacterium overgrowth is a common problem in Agrobacterium-mediated plant transformation. To suppress the Agrobacterium overgrowth, various antibiotics have been used during plant tissue culture steps. The antibiotics are expensive and may adversely affect plant cell differentiation and reduce plant transformation efficiency. The SacB-SacR proteins are toxic to most Agrobacterium tumefaciens strains when they are grown on culture medium supplemented with sucrose. Therefore, SacB-SacR genes can be used as negative selection markers to suppress the overgrowth of A. tumefaciens in the plant tissue culture process. We generated a mutant A. tumefaciens strain GV2260 (recA-SacB/R) that has the SacB-SacR cassette inserted into the bacterial genome at the recA gene locus. The mutant Agrobacterium strain is sensitive to sucrose but maintains its ability to transform plant cells in both transient and stable transformation assays. We demonstrated that the mutant strain GV2260 (recA-SacB/R) can be inhibited by sucrose that reduces the overgrowth of Agrobacterium and therefore improves the plant transformation efficiency. We employed GV2260 (recA-SacB/R) to generate stable transgenic N. benthamiana plants expressing a CRISPR-Cas9 for knocking out a WRKY transcription factor.